2020
DOI: 10.3390/foods9111713
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of Vitamin D2 in the White Button Mushroom (Agaricus bisporus) by UV-B Irradiation and Jet-Milling for Its Potential Use as a Functional Ingredient

Abstract: The objective of this study was to amplify vitamin D2 in white button mushrooms using ultraviolet (UV-B) irradiation and to prepare a vitamin D2-fortified superfine mushroom powder through jet milling. Mushrooms irradiated with UV-B for 30 min had a vitamin D2 concentration of 8.19 μg/g, an amount about 400 times greater than that of the control (0.02 μg/g). The vitamin D2-fortified mushrooms were then freeze-dried and conventionally ground or jet-milled to obtain coarse (Dv50 = 231 μm), fine (Dv50 = 106.3 μm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…Results indicated that UV‐B irradiation did promote the conversion of ergosterol to vitamin D 2 and straw mushroom had the potential to become a nutritious food rich in vitamin D 2. Similar results have been reported for other mushrooms (Heo et al, 2020; Nzekoue et al, 2022). Previous studies were found that exposure of mushrooms to UV irradiation increased vitamin D 2 content and was often accompanied by a decrease in ergosterol content (Jiang et al, 2020).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Results indicated that UV‐B irradiation did promote the conversion of ergosterol to vitamin D 2 and straw mushroom had the potential to become a nutritious food rich in vitamin D 2. Similar results have been reported for other mushrooms (Heo et al, 2020; Nzekoue et al, 2022). Previous studies were found that exposure of mushrooms to UV irradiation increased vitamin D 2 content and was often accompanied by a decrease in ergosterol content (Jiang et al, 2020).…”
Section: Resultssupporting
confidence: 90%
“…Similar results have been reported for other mushrooms (Heo et al, 2020;Nzekoue et al, 2022). Previous studies were found that exposure of mushrooms to UV irradiation increased vitamin D 2 content and was often accompanied by a decrease in ergosterol content (Jiang et al, 2020).…”
Section: Vitamin D 2 and Ergosterol Contentsupporting
confidence: 89%
“…A higher radiation dose than used in this study would have generated greater amounts of the D vitamers, at a concentration potentially suitable for use as a powdered supplement. UV-irradiated whole, sliced or powdered dried mushrooms can be used as a supplemental vitamin D food product or an ingredient in functional foods, suited to those at a high risk of vitamin D deficiency [ 39 ]. The European Food Safety Authority has stated that UV-irradiated powdered mushrooms can be used as a novel food ingredient providing supplemental vitamin D 2 [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dried wild mushrooms and sun-dried commercial mushrooms may also have the potential to be a source of D vitamers when cooked (Huang et al, 2016;Rangel-Castro, Staffas, & Danell, 2002). Commercial packs of dried mushrooms usually state a serving size as 10-30 g. Using an example serving size of 20 g, the UV-irradiated, air-dried then rehydrated control samples would provide approximately 140 µg D 2 , which is higher than the recommended daily requirements for vitamin D. The UV dose could be modified to generate amounts of vitamin D to suit the local requirement for dietary vitamin D, or the dried mushrooms could be ground into a powder to provide a supplemental source of vitamin D for use in dishes such as soups and stews, or as an ingredient in manufactured food products (Heo, Kim, Park, & Lee, 2020). The European Union has approved the sale of fresh UV-exposed mushrooms provided that the tolerable upper intake limits of vitamin D set by the European Food Safety Authority (EFSA) are not exceeded (European Commission, 2018).…”
Section: Bakingmentioning
confidence: 99%